Case Report: Molecular and Pathological Investigations of Zoonotic Anatrichosoma Spp.-Induced Ulcerative Pododermatitis in a Domestic Cat in Thailand - Jitsamai, Wanarit; Kesdangsakonwut, Sawang; Srirat, Thanakorn; Taweethavonsawat, Piyanan (Frontiers in Veterinary Science, 2021)
Anatrichosoma spp. is a group of trichuroid nematodes that mainly infect non-human primates and domestic cats. The lifecycle of these nematodes remains unclear. In non-human primates, Anatrichosoma spp. were found in the nasal cavity. However, ulcerative dermatitis has been reported in infected cats. An adult, intact, female domestic short-haired cat was presented with ulcerative pododermatitis of all limbs. Punch biopsy was performed at the edge of the ulcerative wound for histopathological investigation and showed necrosis and infiltration of inflammatory cells around the nematode-like lesion. Eggs with Capillaria-like characteristics were present. Tissue sections were subjected to DNA extraction and PCR targeting 18S rRNA, using primers designed from Anatrichosoma 18S rRNA. The phylogenetic tree revealed that DNA obtained from the lesion of the domestic cat was grouped with Anatrichosoma spp. from the olive glass mouse (Abothirx olivacea), Capillaria plica and Eucoleus aerophilus, both from the red fox (Vulpes Vulpes). The study is the first report of feline anatrichosomiasis in Thailand, and we present both pathological findings and molecular evidence. The cat was successfully treated with emodepsine/praziquantel. The skin lesion recovered within 3 days after anthelmintic treatment. Because Anatrichosoma spp. have been reported in humans, the zoonotic potential of this parasite should be considered.